The MURAL collection of prostate cancer patient-derived xenografts enables discovery through preclinical models of uro-oncology - Gail P. Risbridger (Nature Portfolio, 2021)
The prognosis of castration-resistant prostate cancers remains dismal, but accurate preclinical models can lead to effective therapies. Here the Melbourne Urological Research Alliance establish prostate cancer patient-derived xenografts, use the tumors for organoids and single-cell RNA-seq, and show the efficacy of PARP inhibitor combination treatments.